Genome-Wide Identification and Characterization of HSP90-RAR1-SGT1-Complex Members From Arachis Genomes and Their Responses to Biotic and Abiotic Stresses - Yuan, Cuiling; Li, Chunjuan; Zhao, Xiaobo; Yan, Caixia; Wang, Juan; Mou, Yifei; Sun, Quanxi; Shan, Shihua (Frontiers in Genetics, 2021)
The molecular chaperone complex HSP90-RAR1-SGT1 (HRS) plays important roles in both biotic and abiotic stress responses in plants. A previous study showed that wild peanut Arachis diogoi SGT1 (AdSGT1) could enhance disease resistance in transgenic tobacco and peanut. However, no systematic analysis of the HRS complex in Arachis has been conducted to date. In this study, a comprehensive analysis of the HRS complex were performed in Arachis. Nineteen HSP90, two RAR1 and six SGT1 genes were identified from the allotetraploid peanut Arachis hypogaea, a number close to the sum of those from the two wild diploid peanut species Arachis duranensis and Arachis ipaensis. According to phylogenetic and chromosomal location analyses, thirteen orthologous gene pairs from Arachis were identified, all of which except AhHSP90-A8, AhHSP90-B9, AdHSP90-9, and AiHSP90-9 were localized on the syntenic locus, and they shared similar exon-intron structures, conserved motifs and expression patterns. Phylogenetic analysis showed that HSP90 and RAR1 from dicot and monocot plants diverged into different clusters throughout their evolution. Chromosomal location analysis indicated that AdSGT1 (the orthologous gene of AhSGT1-B3 in this study) might provide resistance to leaf late spot disease dependent on the orthologous genes of AhHSP90-B10 and AhRAR1-B in the wild peanut A. diogoi. Several HRS genes exhibited tissue-specific expression patterns, which may reflect the sites where they perform functions. By exploring published RNA-seq data, we found that several HSP90 genes play major roles in both biotic and abiotic stress responses, especially salt and drought responses. Autoactivation assays showed that AhSGT1-B1 could not be used as bait for yeast two-hybrid (Y2H) library screening. AhRAR1 and AhSGT1 could strongly interact with each other and interact with AhHSP90-B8. The present study represents the first systematic analysis of HRS complex genes in Arachis and provides valuable information for functional analyses of HRS complex genes. This study also offers potential stress-resistant genes for peanut improvement.